Extraction and characterization of amino acids and proteins from wastes of threadfin bream, Nemipterus japonicus (Bloch, 1791) - Yahaya, Noorsuliya Raihan (2019)
Fish such as Nemipterus japonicus is over-exploited in Malaysia and the amounts of this fish species processing wastes are staggering. The wastes are land-filled, ground and discarded or otherwise denied from human or animal consumptions, even though the wastes are still rich in proteins. This is due to the lack of methodologies to recover proteins from wastes from this species. Therefore, this study aimed at extraction of protein from the wastes of the threadfin bream, Nemipterus japonicus using pH shift solubilization and precipitation processes and evaluation of the influencing factors on protein extraction. Towards this objective, the wastes of head, skin and internal organs were collected and their nutritional composition evaluated. Furthermore, the ratio of waste: water for protein extraction was screened and the effect of pH, centrifugation speed and time on protein solubility rate, the amino acid composition and the molecular weight of proteins via SDS-PAGE were determined. Results demonstrated that moisture was the highest percentage (~70-78%) of all wastes. Highest protein content (19.67±1.10%), fat content (1.81±0.09%) and carbohydrate content (4.43±0.23%) were observed in skin, head and internal organs, respectively. The optimum ratio of waste: water for protein extraction is 1:9 for head, 1:8 for internal organs and 1:6 for skin. The protein extraction efficiently for all three samples were high at pH 3 and pH 12. Protein solubility increased with increased centrifugation speed up to 10,000 ×g, and there was no significant difference (P>0.05) between the protein solubility at 10,000 ×g and 20,000 ×g. Furthermore, there was significant difference (P<0.05) between protein solubility with increased centrifugation time. There is no significant difference (P>0.05) in protein yield between the alkaline and the acid process for heads and skin while protein yield in the alkaline and acid process for internal organ is significantly different (P<0.05). Alkaline process showed a remarkably higher amino acid content as compared to that of acid version. Glutamic acid and lysine were found higher compared to other amino acids. The molecular weight of proteins isolated in this study were low (<100 KDa).